FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBAYARAN NON TUNAI PADA E-COMMERCE - Hadi, T Saiful; Kismawadi, Early Ridho; Chalil, Rifyal Dahlawy; Bahri, M Irvani (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
This study aims to determine the effect of consumer knowledge, the ease and features of the service on the decision to use. A total of 100 respondents were involved in this study using purposive sampling technique. Respondents were selected based on the criteria, namely, e-commerce users at least 5 times who used Shopee, Tokopedia and Lazada in the past year. Multiple Linear Regression Analysis was used in this study as a method to analyze data using SPSS 16.0 (Statistical Package for Social Science) software. The results of this study indicate that: (1) Consumer knowledge has a positive and significant effect on decisions to use non-cash payments in e-commerce, indicated by the value of the income coefficient (X1) which is positive, namely 2.507 and the p-value is less than the significance level (0.014 < 0.05). (2) Ease has a positive and significant effect on the decision to use non-cash payments in e-commerce, indicated by the value of the convenience coefficient (X2) which is positive, namely 3.023 and the p-value is less than the significance level (0.003 < 0.05). (3) Service features have a positive and significant effect on the decision to use non-cash payments in e-commerce, as indicated by the service feature coefficient value (X3) which is positive, namely 3.409 and the p-value is less than the significance level (0.001 < 0.05). And the coefficient of determination (R2) is 0.341 or 34.1%. This value indicates that 34.1% of usage decisions are influenced by consumer knowledge, convenience and service features, while the remaining 65.9% is influenced by independent variables that are not examined.